Impact of unanticipated and backhand area smash landing on the lower limb biomechanics of female badminton players - He, Zhanyang; Fang, Zeqi; Ye, Haoxiang; Su, Sujing (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundIn badminton, lower limb injuries frequently occur during unanticipated smash landing movements. Additionally, the risk of lower limb injuries may vary depending on different landing strategies. This study aims to investigate the impact of unanticipated factors and two types of smash actions in the backhand area on lower limb biomechanics.MethodA motion capture system and force plates were used to collect biomechanic data of 13 female athletes (age: 21.2 ± 1.9 years; height: 167.1 ± 4.1 cm; weight: 57.3 ± 5.1 kg) during backhand rear-court jump smash (BRJS) and backhand lateral jump smash (BLJS) in both anticipated and unanticipated conditions. Unanticipated tasks were conducted by having the athletes perform a random number of specific badminton corner drills, followed by a random movement command given by a signboard and a shuttlecock being launched towards the left half-court by a machine. Waveform analysis was performed using Statistical Parametric Mapping, and discrete parameters were analyzed using a 2 × 2 repeated measures ANOVA.ResultsThe results indicated that under unanticipated conditions, both BRJS and BLJS led to higher vertical instantaneous load rates (p = 0.003, ηp2 = 0.314) and knee extension moments (p = 0.013, ηp2 = 0.231) at initial contact (IC). The main effect results indicated that BRJS caused greater knee abduction angles (p = 0.03, ηp2 = 0.182) and knee adduction moments (p = 0.010, ηp2 = 0.248) at IC than BLJS, while the interaction effects showed that BRJS had a greater frontal plane center of pressure displacement under unanticipated conditions (p = 0.041, ηp2 = 0.186). BLJS showed greater knee extension moments (p = 0.013, ηp2 = 0.231) and smaller knee (p = 0.002, ηp2 = 0.347) and hip (p < 0.001, ηp2 = 0.491) flexion angles at IC compared to BRJS. Additionally, BLJS demonstrated higher peak ankle internal rotation moments (p = 0.018, ηp2 = 0.212) than BRJS, with a greater peak ankle inversion moment under unanticipated conditions.ConclusionUnanticipated factors significantly impacted the biomechanics of both smash landing actions, potentially increasing the risk of ACL injuries. Moreover, unanticipated factors may increase the risk of ankle sprains during the BLJS movement.